Transformasi Teknologi Pengolahan dan Pengemasan Sale Pisang Berbasis Pengering Hybrid untuk Peningkatan Mutu dan Daya Saing Produk di Desa Pengadangan, Lombok Timur - Widhiantari, Ida Ayu; Cicilia, Siska; Dewi, Endang Purnama; Firmansyah, Surya Ananda; Sukma, Dinda Galuh (Universitas Mataram, 2025)
Pengadangan Village, Pringgasela District, East Lombok Regency, West Nusa Tenggara Province has a superior commodity in the form of bananas. Despite having great potential, the banana sale industry in Pengadangan Village faces various challenges that hinder the development and improvement of product quality, including the process of drying banana sales is still highly dependent on sunlight, the packaging of banana sale products is still relatively simple and marketing problems that are currently still conventionally sold in the market and in stalls. The application of solar energy-based hybrid drying technology that is more efficient and environmentally friendly is a solution for Bale Sentosa MSMEs in overcoming the problem of the drying process in making banana sales. So far, MSME owners have carried out a traditional drying process where bananas are sold in the open in the open in direct sunlight. This condition causes banana sales to be easily contaminated by animals such as flies and dust. The service team provides solar energy-based hybrid system drying technology to improve the quality of banana sale products. The next process is the packaging of banana sale using paper standing pouch packaging equipped with brand labels. The owner of Bale Sentosa MSMEs is very happy and satisfied with the existence of solar energy-based hybrid drying because in addition to being very useful in overcoming the shortcomings of conventional method drying, the owner of Bale Sentosa MSMEs also gains an understanding of simple technology in drying using hybrid-based drying solar energy. In addition, the introduction of packaging is felt to be very useful because by providing information on packaging and by using modern packaging, the market can be expanded, not only in the surrounding area.